Annotated list of orchidaceae types of the Bennett collection at the forestry Herbarium MOL - Trujillo, Delsy (2014)
An annotated list of the original material of 183 Orchidaceae species of the Bennett’s collection at the Forestry herbarium of the University Agraria La Molina is presented. The annotated list includes collection data, information on locations of the type material in other herbaria and the currently accepted name for each species. Seventy two lectotypes are designated; and a new species and a new combination are validated under the current code of nomenclature (International Code of Nomenclature -Melbourne Code).